Aplikasi Pupuk Organik dan NPK untuk Meningkatkan Pertumbuhan Vegetatif dan Produksi Buah Terong Hijau - Ahmad Raksun; Lalu Japa; I Gde Mertha (Jurnal Penelitian Pendidikan IPA, 2019)
Abstract: Research has been conducted on the application of organic and NPK fertilizer to increase the growth and yield of green eggplant which aims to find out (1) the influence of organic fertilizer on vegetative growth and yield of Green eggplant, (2) the effect of NPK fertilizer on vegetative growth and yield of Green Eggplant, (3) the effect of interaction between organic fertilizer and NPK fertilizer on vegetative growth and yield of Green Eggplant. A Factorial design was used which consisted of 2 factors. The first factor is the dose of organic fertilizer and the second factor is the dose of NPK fertilizer. The treatment of organic fertilizer consists of 4 levels, namely: P0 = without giving organic fertilizer (control), P1 = giving 0.5 kg organic fertilizer /1 m2 land, P2 = giving 1.0 kg organic fertilizer /1 m2 land, P3 = giving 1.5 kg organic fertilizer/1 m2 land. NPK fertilizer consists of 5 levels namely: N0 = without NPK fertilizer (control), N1 = giving 5 gr NPK fertilizer/plant, P2 = giving 10 gr NPK fertilizer/plant, P3 = giving 15 gr NPK fertilizer/plant, P4 = giving 20 gr NPK fertilizer/plant. Growth parameters were stem height and length of green eggplant leaves. Yield parameters were fruit length and green eggplant fruit weight. Data were analyzed by using ANOVA. The results showed that the application of organic fertilizer has a significant effect on the growth and yield of green eggplant. The application of NPK fertilizer has a significant effect on the growth and yield of green eggplant. The interaction of organic fertilizer and NPK fertilizer did not significantly affect the growth and yield of green eggplant. Key Words: organic fertilizer; NPK fertilizer; growth and production of green eggplant.